A straightforward enantioselective synthesis of F17807. Issue 50 (16th December 2015) - Alliot, Julien; Gravel, Edmond; Buisson, David-Alexandre; Larquetoux, Laurent; Nicolas, Marc; Doris, Eric
Abstract: An efficient approach for the enantioselective synthesis of the 1, 4-benzodioxane F17807 drug is reported. The developed route relied on two key steps, namely SN Ar and Mitsunobu reactions, which permitted a straightforward access to the title compound with full preservation of the enantiomeric excess throughout the synthetic sequence. Graphical abstract: